Analisis Pengendalian Internal dalam Sistem Pengendalian Manajemen pada Proses Penjualan dan Penerimaan Kas: Studi Kasus Bengkel Mobil XYZ - Rizna Kusuma Dewi Al-ayubbi; Dian Hakip Nurdiansyah; Venni Avionita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze internal control as an integral part of the Management Control System (MCS) in the sales and cash receipts processes at XYZ Auto Repair Shop. A descriptive qualitative approach was employed through interviews, observations, and documentation involving the owner, administrative staff, and cashier. The findings indicate that sales and cash receipt activities are still conducted manually without adequate segregation of duties, sequential document numbering, and daily cash reconciliation. An evaluation based on the COSO Internal Control–Integrated Framework reveals weaknesses particularly in control activities and monitoring components. These conditions contribute to recording delays, recurring cash discrepancies, and operational inefficiencies. The study recommends implementing a computerized recording system, establishing clear segregation of duties, applying systematic document numbering, and strengthening daily reconciliation procedures to enhance accuracy and control effectiveness. The findings emphasize that structured internal control plays a crucial role in supporting the effectiveness of MCS in service-oriented businesses.